THE PREPARATION AND CHARACTERIZATION OF SOME NOVEL FEROCENIL DERIVATIVES - Ilić Komatina, Danijela; Minić Jančić, Aleksandra; Bugarinović, Jovana; Stevanović, Dragana (Bulletin of Natural Sciences Research, 2021)
This paper provides a report on an easily performable synthesis via one-pot reaction, between the newly synthesized 3-arylamino-1-ferrocenylpropan-1-ols and PhNCO. We have used the acetic acid as the catalyst and ultrasound irradiation as the reaction promoter. We have evaluated the reaction score on three examples. In order to gain a more comprehensive insight into the role of α-ferrocenyl carbocation, we have described a plausible mechanism of the transformations in question. Moreover, we have purified the prepared by using column chromatography. Besides, we provide a detailed characterization of the new compounds (products and starting material), which was performed by IR, NMR and elemental analyses.